Computer accounting with Microsoft office accounting 2007 - Yacht, Carol (McGraw-Hill/Irwin, 2007)
The latest textbook offering from two of the most prolific writers in the computer accounting field provides concise and comprehensive instruction on how to use new accounting software from Microsoft in conjunction with Microsoft Office applications. The directions are interesting and easy-to-use, and are supported by in-depth analysis of up-to-date business situations and reports. Yacht and Crosson have simplified the installation process so students are ready to start working with the software in as short a time as possible. Students learn how to harness the power of Microsoft Office to link data between applications, leveraging reports and analysis opportunities and reducing errors.